O065 The impact of breaking up sitting on vigilant attention during the workday when sleep restricted. (9th November 2022) - Gupta, C; Ferguson, S; Vandelanotte, C; Duncan, M; Tucker, P; Lastella, M; Tuckwell, G; Vincent, G
Abstract: Introduction: Sleep restriction is associated with impairments to cognitive performance. A current strategy to improve cognitive performance at work is breaking up prolonged sitting with light-intensity walking. However, it is unknown whether this strategy can counteract the impact of sleep restriction. This study investigated the effect of breaking up sitting on cognitive performance under conditions of sleep restriction. Method: 84 healthy adults (age M± SD: 23.1±4.5 years; 41 females) participated in a 7-day laboratory study, with 5 simulated workdays (0900-1700). Participants were randomly allocated to a condition: Breaking up sitting and 9-h sleep (Break9; n=20), Breaking up sitting and 5h sleep (Break5; n=20), Sedentary and 9-h sleep (Sit9; n=22), Sedentary and 5-h sleep (Sit5; n=22). Sleep opportunity prior to each workday was 9-h (2200-0700) or 5-h (0200-0700) depending on condition. Every 30-min during the workday participants in the breaking up sitting conditions completed 3-min bouts of light-intensity walking, while participants in the sedentary conditions remained sitting. At 0900, 1100, 1300, 1500, and 1700, participants completed a 10-min Psychomotor Vigilance Task and the Karolinska Sleepiness Scale. Results: Mixed model ANOVAs revealed no significant 2-way or 3-way interactions between condition (Break9, Break5, Sit9 and Sit5), time of day, and workday for vigilant attention (reciprocal mean response time and mean lapses) or subjective sleepiness. Discussion: Breaking up prolonged sitting with light-intensity walking did improve cognitive performance. Higher doses of physical activity may be needed to counteract the effects of sleep restriction on cognitive performance. Findings highlight the acute cognitive deficits associated with inadequate sleep.